Do orbital floor plates adequately protect against serious secondary injury?. Issue 6 (July 2019) - Zaggut, A.; Perry, M.
Abstract: Reconstruction of the orbital floor is common in cases of trauma and a variety of alloplastic materials, including titanium, can be used. However, we know of no reports about what happens to these materials if there is a second injury to the surgical site. This pilot study on six human cadavers (12 orbits) was therefore designed to investigate the possible outcomes should this occur. A "blowout fracture" was created in each orbit, which was then repaired using a preformed titanium implant. In two orbits, two implants were placed without fixation. The remaining implants were secured to the anterior orbital floor with a single screw, which was placed laterally or medially. A second impact sufficient to fracture the zygomaticomaxillary complex was then applied and its effect on the implants noted.